APLIKASI PENDIDIKAN KECAKAPAN HIDUP (LIFE SKILLS) BERBASIS PENDIDIKAN AGAMA ISLAM - Khairuddin Nur (UNISAN JURNAL, 2024)
The point of this examination is to decide the utilization of fundamental abilities in light of Islamic strict schooling. what endeavors are made to execute fundamental abilities in view of Islamic strict training?; (3) what are the deterrents in carrying out fundamental abilities in light of Islamic strict schooling. Thus, in this composing the kind of examination that the creator utilizes is a subjective illustrative exploration strategy, which stresses the force of direct field perception and afterward breaking down information from existing information sources. From the consequences of the examination the creator reaches the accompanying determinations: The application (execution) of fundamental abilities schooling in light of Islamic strict training, SD Tahfiz Qur’an Cita Mulia Lenteng Agung Jakarta Selatan - Subang is partitioned into two, to be specific: a. Giving abilities schooling that imparts strict qualities, for example, beginning learning with an initial petition, joining understudies impacted by fiascos, etc. B. Giving abilities schooling through dominating certain or exceptional abilities, in particular capacities in the fields of PCs and dialects. Endeavors made to carry out fundamental abilities instruction in view of Islamic strict schooling include: . Giving opportunity to do fundamental abilities schooling, for example, directing and going with understudies in investigating information in the field of data and innovation, extending the items in the Koran and applying language abilities, in particular English and Arabic, as well as completing studio abilities and others. . B. Giving supporting to the execution of abilities schooling, both material and non-material, which is standard or casuistic in nature. C. Change of passage plan from evening to morning, as far as love understudies can be instructed to play out the Dhuha petition, read the Koran with the instructor for 10 minutes. D. Understudies are offered the chance to seek after a more significant level of schooling, to foster their capacities so they can change their abilities to understudies all the more ideally. e. Endeavors on the data innovation side, SD Tahfiz Qur’an Cita Mulia Lenteng Agung Jakarta Selatanis outfitted with a web organization and a PC lab that can be involved everyday for understudy practice.